(untitled) (The Macau Ricci Institute Journal, 2020)
I suggest three key ideas that are crucial to change the economic paradigm towards an economy oriented to the common good based on solidarity and fairness. These are frugality in consumption and production, acknowledging the intrinsic value of nature, and developing wellbeing oriented businesses.